Alternative framework in "body coordination" topic: A progress report for interior of Malaysia - Davy Seligin; Mohd. Zaki Ishak; Jominin Goropos (Redfame Publishing, 2015)
This preliminary study was conducted in interior of Malaysia. The study employed the Body Coordination Two Tier Concept Test to assess students’ understandings of body coordination topic. The test consisted of 14 questions as two tier question style. The students needed to select the answer and write down the justifications of each answer. Interview was conducted with six students to get in-depth opinion about Body Coordination.